THE PROLIFERATION OF CORRUPT ACTIVITIES IN PUBLIC HEALTH SYSTEMS DURING THE GLOBAL COVID 19 PANDEMIC - Meini, Bruno (Journal of Anti-Corruption Law, 2023)
The health-care sector should aim at maintaining and improving the quality of life and individual welfare of each patient, but this is difficult when corruption pervades one or more of the pillars of health-care services such as the structure, organisation, financing, and/or delivery systems. Health systems are particularly susceptible to corruption due to the very large amounts of monetary resources involved, information asymmetries, the large number and wide distribution of actors, system complexity and fragmentation, and the increasingly advanced international supply chain of medicines and medical equipment. Corruption weakens the effective functioning of health systems and usually contributes to their progressive deterioration.